A splicing site change between exon 5 and 6 of the nuclear-encoded chloroplast-localized HvYGL8 gene results in reduced chlorophyll content and plant height in barley - Xia, Xue; Liu, Lei; Cai, Kangfeng; Song, Xiujuan; Yue, Wenhao; Wang, Junmei (Frontiers in Plant Science, 2023)
The chloroplast is an important cellular organelle and metabolic hub, which is not only responsible for plant photosynthesis but is also involved in the de novo biosynthesis of pigments, fatty acids, and hormone metabolisms. Several genes that are responsible for rice leaf color variations have been reported to be directly or indirectly involved in chlorophyll biosynthesis and chloroplast development, whereas a few genes have been functionally confirmed to be responsible for leaf color changes in barley at the molecular level. In this study, we obtained a yellow leaf and dwarf ygl8 mutant from the progeny of Morex (a variety of barley) seeds treated with EMS. We performed bulked-segregant analysis (BSA) and RNA-seq analysis and targeted a UMP kinase encoding gene, YGL8, which generated a splicing site change between exon 5 and 6 of YGL8 due to a G to A single-nucleotide transition in the 5th exon/intron junction in the ygl8 mutant. The splicing site change between exon 5 and 6 of YGL8 had no effects on chloroplast subcellular localization but resulted in an additional loop in the UMP kinase domain, which might disturb the access of the substrates. On one hand, the splicing site change between exon 5 and 6 of YGL8 downregulated the transcriptional expression of chloroplast-encoded genes and chlorophyll-biosynthesis-related genes in a temperature-dependent manner in the ygl8 mutant. On the other hand, the downregulation of bioactive GA-biosynthesis-related GA20ox genes and cell-wall-cellulose-biosynthesis-related CesA genes was also observed in the ygl8 mutant, which led to a reduction in plant height. Our study will facilitate the understanding of the regulation of leaf color and plant height in barley.